The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1128/jcm.01571-14
|View full text |Cite
|
Sign up to set email alerts
|

Precision of Vancomycin and Daptomycin MICs for Methicillin-Resistant Staphylococcus aureus and Effect of Subculture and Storage

Abstract: dThe reproducibility of vancomycin and daptomycin MICs, measured by broth microdilution (BMD) and Etest, was prospectively assessed for 10 methicillin-resistant Staphylococcus aureus (MRSA) isolates from the blood samples from patients on vancomycin therapy. The isolates were tested at the time of isolation from blood and following 5, 10, and 20 subcultures and at 1, 3, 6, and 12 months of storage at ؊70°C. The MICs were determined by Etest and BMD using two different manufacturers (BBL and Difco) of cation-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…For example, colistin MICs for P. aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii have been shown to decrease from a resistant/non-wild-type phenotype to a susceptible/wild-type phenotype after frozen storage (8). Similarly, vancomycin MICs for Staphylococcus aureus have been shown to decrease after 1 year of frozen storage (9). Details to be included in Materials and Methods for the evaluation, regarding how the cAST was performed, are outlined in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…For example, colistin MICs for P. aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii have been shown to decrease from a resistant/non-wild-type phenotype to a susceptible/wild-type phenotype after frozen storage (8). Similarly, vancomycin MICs for Staphylococcus aureus have been shown to decrease after 1 year of frozen storage (9). Details to be included in Materials and Methods for the evaluation, regarding how the cAST was performed, are outlined in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…On one hand, to deepen this question, we performed the antibacterial testing of the composite pastes in vitro . On the other hand, with the release totaling ~ 2 % of the total drug content in the first 24 h, equaling 2 mg/g of the paste, it would take only 1 g/dm 3 of the paste to reach the uppermost end of the MIC for vancomycin against methicillin-resistant S. aureus (2 μg/ml) 49 in this period of time. Such an absence of the burst release indicates that the antibiotic is almost completely confined to the interior of the hardened paste and that the degradation of the paste in an aqueous environment will precondition its antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…In MRSA strains with heterogenous resistance, after separation from blood and sub-culture on drug-free, nutrient-rich medium, the lower MICs observed in isolates after sub-culturing of positive blood cultures may reflect a change in the MRSA population being tested. Although a previous study reported no differences in VAN MICs after repeated sub-cultures, that study did not compare sub-cultured MRSA and direct VAN MIC testing [11].…”
Section: Discussionmentioning
confidence: 99%